Non-Arabic students’ reading preferences for e-learning programs - Zainuddin, Nurkhamimi (2011)
Non-Arabic students are increasingly depending on e-learning programs. Readability of e-learning programs text has been shown to be influenced by a number of typographical variables including text type and size, screen line length, white space, etc. therefore, it is very important to improve the reading efficiency and satisfaction. Combination of inappropriate screen line length with the wrong font type and size can slowdown reading and comprehension. Following simple design guidelines can improve students reading performance and satisfaction. However, guidelines that are built for English script cannot be simply applied for Arabic script due to differences in letters occupation and writing direction. The aim of this paper was to build a set of guidelines that can be used for Arabic e-learning programs for Non-Arabic students. An e-story was designed to be tested for the best font type and size combination and the preferred screen line length. Results indicated that Non-Arabic students preferred the use of Simplified Arabic with size 14-point size to ease and speed the reading. Moreover, they found Simplified Arabic with 14-point font size is more attractive. Results indicated that most of the participants preferred to read with full screen line length.